Cover Feature: Different Enzyme Conformations Induce Different Mechanistic Traits in HIV‐1 Protease (Chem. Eur. J. 42/2022). Issue 42 (6th July 2022) - Coimbra, João T. S.; Neves, Rui P. P.; Cunha, Ana V.; Ramos, Maria J.; Fernandes, Pedro A.
Abstract : Using different starting conformations and quantum mechanics/molecular mechanics (QM/MM) molecular dynamics simulations, this study addressed the convergence of activation free energies and the mechanistic divergence of the first step catalysed by HIV‐1 protease. More information can be found in the Research Article by P. A. Fernandes and co‐workers (DOI: 10.1002/chem.202201066 ).